PENERAPAN METODE FINITE STATE MACHINE (FSM) PADA GAME ROLE PLAYING GAME (RPG) INK JOURNEYS - Egha Pacsi Yudha Perdana; Sri Winarso Martyas Edi (IT Explore: Jurnal Penerapan Teknologi Informasi dan Komunikasi, 2024)
Lately, folklore is no longer well known by many people. The abundance of entertainment available on the internet has replaced entertainment in the previous era, including folklore. The game "Ink Journeys" is a game created in this study by presenting folklore as the story material in it. This game focuses on the main character who can enter a book containing a collection of folklore in Indonesia. The research began with collecting folklore circulating on the internet, then adjusted to the main story in the game. This study developed a method for implementing Finite State Machine. Different from previous research, Finite State Machine is implemented not only in character and object dialogues, but also applies Finite State Machine to the map area. With the Finite State Machine method, game makers will be more structured and focused when creating programs in the game. As for the players, players will be met with choices that will affect the story in the game. This game can only be played on Android and only has one folklore adapted into the game.